A Framework for BIM-Enabled Life-Cycle Information Management of Construction Project. (22nd August 2014) - Xu, Xun; Ma, Ling; Ding, Lieyun
BIM has been widely used in project management, but on the whole the applications have been scattered and the BIM models have not been deployed throughout the whole project life-cycle. Each participant builds their own BIM, so there is a major problem in how to integrate these dynamic and fragmented data together. In order to solve this problem, this paper focuses on BIM-based life-cycle information management and builds a framework for BIM-enabled life-cycle information management. To organize the life-cycle information well, the information components and information flow during the project life-cycle are defined. Then, the application of BIM in life-cycle information management is analysed. This framework will provide a unified platform for information management and ensure data integrity.